New technologies and human dignity in current medicine - Cometta, Mosè (Research and Humanities in Medical Education, 2021)
This paper addresses the problems and challenges posed by the development of digital medicine as seen from the perspective of the medical humanities. Beyond the obvious advantages of technological innovation, the paper emphasizes the importance of an in-depth debate on the risks of patient quantification and growing inequalities. The education of new health professionals is a key element for the success of this debate.